Effectiveness of Modified Learning Media on Student Creativity - Akin, Yogi; Suherman, Ayi; Safari, Indra; Susilawati, Dewi; Sudrazat, Adang; Nugraha, Reshandi; Brilian, Mohamad (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
This study aimed to determine the influence of modified learning media on the student creativity. The research method employed an experimental method with a pretest-posttest control group design. The sample of this study consisted of PETE for Elementary School students selected through purposive sampling. The research instrument utilized a creativity questionnaire. Based on the data analysis, the significance value was 0.019, indicating a significant influence of modified learning media on the student creativity. This study concludes that there was a significant impact of modified learning media on the student creativity. Modifying learning media can be considered a viable alternative in education to enhance creativity and other cognitive components.